FDI Spillovers and High-Growth Firms in Developing Countries - Reyes, Jose-Daniel (World Bank, Washington, DC, 2017)
This paper evaluates the heterogeneous impact of spillovers from multinational corporations (MNCs) to domestic enterprises in the developing world. It empirically investigates two transmission channels of knowledge spillovers. First, direct contractual linkages between indigenous firms and MNCs. Second, indirect demonstration effects accrued by domestic firms by imitating foreign technologies either through observation or by hiring workers trained by MNCs. The paper focuses on the impact of spillovers on high-growth firms, which are enterprises with high job creation rates and, therefore, assumed to have high absorptive capacities. The paper also evaluates spillovers stemming from MNCs with different motivations to invest in developing countries. Employing a survey of around 71,000 firms across 50 sectors in 122 developing countries, the paper shows that high-growth firms internalize spillovers through both avenues and that contractual linkages are the most powerful transmission channel. FDI embedded in global value chains generates larger spillovers to high-growth domestic firms than investment that seeks to serve the host economy. There is no evidence that natural resource-seeking FDI generates spillovers. The results have important implications for policy design, as public funding in developing countries is often directed to support programs that seek to connect domestic suppliers with MNCs.